2004
DOI: 10.1097/01.ccm.0000139694.47326.b6
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction rate in acute pulmonary edema: Noninvasive pressure support ventilation versus continuous positive airway pressure

Abstract: NIPSV proved to be equally effective in improving vital signs and ventilation without increasing acute myocardial infarction rate in patients with nonischemic acute pulmonary edema in comparison to CPAP alone. However, because the study lacked statistical power and excluded patients with acute coronary syndromes, caution is still advised when applying NIPSV to the latter subgroup of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(59 citation statements)
references
References 25 publications
5
48
0
5
Order By: Relevance
“…Recently, Nouira et al, [20] showed that Bi-PAP improves respiratory failure, while, Masip et al, [21] showed a decrease in intubation rate in Bi-PAP group when compared with CPAP. However, other studies [10,22] failed to demonstrate significant differences in vital signs, blood gases, and rate of myocardial infarction between two modes of ventilations and between Bi-PAPA and oxygen therapy [23]. Moreover, Gray et al, [24] did not find the difference in intubation or mortality rates with either CPAP or Bi-PAP compared to oxygen therapy.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…Recently, Nouira et al, [20] showed that Bi-PAP improves respiratory failure, while, Masip et al, [21] showed a decrease in intubation rate in Bi-PAP group when compared with CPAP. However, other studies [10,22] failed to demonstrate significant differences in vital signs, blood gases, and rate of myocardial infarction between two modes of ventilations and between Bi-PAPA and oxygen therapy [23]. Moreover, Gray et al, [24] did not find the difference in intubation or mortality rates with either CPAP or Bi-PAP compared to oxygen therapy.…”
Section: Introductionmentioning
confidence: 88%
“…Many studies revealed that, CPAP improved arterial oxygenation (PaO 2 ), and reduces endotracheal intubation rate [9][10][11] and mortality rate in ACPE [12,13]. However, other studies failed to show these effects [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that these myocardial infarcts preceded inclusion or were the direct result of the ventilator mode was questioned. In a subsequent randomized study, Bellone et al [26], however, concluded that CPAP and NIPPSV were equivalent in terms of clinical parameters improvement, but also in terms of myocardial infarction rate or troponin plasma levels increase. In all subsequent clinical comparisons, both CPAP and NIPPSV proved superior to medical therapy alone in terms of reducing the intubation rate [27,28], without any adverse event rate or outcome differences.…”
mentioning
confidence: 97%